Development of a nurse-led decision counseling program for improving hepatocellular carcinoma screening: A typology-guided feasibility study - Caixia Li; Xiling Lu; Fei Gao; Eunice Lee; Carmen W.H. Chan (Elsevier, 2023)
Objective: Hepatocellular carcinoma (HCC) is frequently diagnosed late. Although ultrasound-based HCC screening is recommended, its effectiveness is restricted by underutilization. This study aimed to develop a nurse-led decision counseling program used to improve HCC screening in patients with hepatitis B and to evaluate its feasibility in terms of process, resources, management, and cultural acceptance. Methods: The nurse-led decision counseling program was developed following the Medical Research Council framework and the preventive health model. Its components were informed by a systematic review and a qualitative study that had explored empirical HCC screening barriers. Guided by typology of Tickle-Degnen, a feasibility study was conducted among twenty eligible patients with hepatitis B, who were randomized to receive the intervention plus usual care or usual care only. Multisets of feasibility data were collected from interviews, field notes, and minutes of discussions with participants, family members, and clinical specialists. Results: The program consists of health education, tailored information, values clarification exercises, and exploring and addressing barriers, which help to achieve informed and value-based HCC screening utilization. Feasibility assessments identified and improved process issues, such as restrictive inclusion criteria and cultural challenges, including (1) default mistrust, (2) discrimination and confidentiality concerns, (3) cultural reluctance to open discussions about HCC screening, and (4) social influence under a collectivist culture. Conclusions: The study informs an innovative feasibility typology for nursing interventions and contributes to a promising, feasible, and culturally relevant intervention to improve HCC screening and prevent advanced diagnosis in hepatitis B-induced HCC in China and other hepatitis B-prevalent Asian countries. Trial registration: Clinicaltrials.gov: NCT04659005.